Situation Report: Hungary, 24 August 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungary in the Computer Age: Prospects and Problems Tourism: The Midyear Picture Constitution Day Worker-Peasant Meetings on Constitution Day Cultural Gap between the Masses and the Elite Preparations for the Co-operative Congresses Ministry of Agriculture and Food Conference FRG Economics Minister Visits Budapest